International Relations of Turkestan Jadids - Murodov Halim Salimovich; Khojaniyozov Jahongir (International Journal Of History And Political Sciences, 2025)
This article covers the formation and development of the jadidism movement on the basis of the educational and cultural ties established by the jadids of Turkestan with foreign countries, foreign education and experience. Through the work of intellectuals such as Abdurauf Fitrat, Munavvarqori Abdurashidkhanov, Fayzulla Khojaev, the role of international experience in national awakening and modernization has been analyzed.It also reveals on a scientific basis the influence of international relations on the development of jadidist ideas.